Sinais de transtorno reativo de vínculo em crianças abrigadas por meio do desenho da figura humana - Melani, Renata Hottum (2010)
This research aimed to investigate signs of Attachment Disorders in sheltered children using the Human Figure Drawing. 25 children (15 males and 10 female), aged 4 to 12 years living in a sheltered home in São Paulo metropolitan area were assessed. The instrument used for assessment was the Human Figure Drawing (HFD), following Koppitz‟s 30 emotional indicators. Results showed that 48% of the assessed children present shyness, withdrawal and lack of aggression, as well as poor social interest, feelings of immobility, despair and inability of going on with self confidence. Another indicator observed in 40% of the children was openly aggression towards the environment and 40% of the children also showed signs of inadequacy or guilt concerning their inability to act correctly or to act in general. Results suggest that some of the children in this sample present significant signs of Attachment Disorder. As diagnosis criteria for the disorder are still lacking precision, more research using the drawing are still needed.